RULES OF DESCENT IN SIXTEENTH CENTURY YUCATAN - Haviland, William A. (Estudios de Cultura Maya, 2013)
University of Vermont Anthropologists have long shown a fascination with the operation of descent as an important principle of social organization. That such principles are strongly linked with subsistence and residence patterns has been repeatedly asserted (c£. Driver 1961: 319-324). Needless to say, when dealing with American Indian societies which were conquered by Europeans over 400 years ago, it is not always easy to learn which descent principles were in force in those societies. Following the discovery of the Americas, a steady stream of books, pamphlets, and letters were produced to satisfy the curiosity of Europeans about the native inhabitants of the new lands. Though many of the earliest chroniclers were educated, none were trained anthropologists, nor did many have the leisure needed to make thorough studies of their subjects. Furthermore, Indians were regarded with various degrees of prejudice, ranging from a sympathetic attitude on the one hand to outright hostility on the other. Then, too, much of the writing of the early chroniclers was biased by a concern with the Indian's soul, the exploitation of his labor, and the conquest of his land. Hence, their efforts do not necessarily provide us with reliable information on descent.